A Burst Phase Analysis Technique for High Precision Time Delay Estimation of Frequency Hopping GSM Signals - Götz, Alexander; Rose, Richard; Zorn, Stefan; Fischer, Georg; Weigel, Robert (Asia-Pacific Microwave Conference (APMC), 2011)
In this paper, a novel burst phase analysis technique for high precision time delay estimation of frequency hopping GSM signals is presented. The technique makes use of the increased bandwidth of frequency hopping waveforms and acquires and processes the signals in a coherent way. This way, the actual applicable bandwidth for time delay estimation and localization purposes is increased significantly. In case of E-GSM 900 systems, up to 35 MHz of bandwidth can be used which enables localization of mobile phones in the order of a few meters. The technique is therefore ideally suited for search and rescue applications. The presented method may also be applied to TETRA, DECT, IEEE 802.15.4 (ZigBee) or IEEE 802.15.1 (Bluetooth) signals.
elib2cris::1512001600,goetz2011b
Keywords: GSM; TDOA; Localization; Frequency Hopping